Complaint Management At Public Hospital Banjarmasin - Ariadi, Herman (Universitas Muhammadiyah Kalimantan Timur, 2023)
The hospital service has been a concern for the public, because they were not satisfied with the service. Complaints were still found consequently, so the clients felt dissatisfied. This study aimed to look at the complaint management at Public Hospital of Dr. H. Moch Anshari Saleh Banjarmasin. This was a qualitative study with phenomenology design. Data collection was undertaken by in-depth interviews with eight participants. The participants of this research were five middle service managers, one middle manager in administration and finance, one head of the complaints unit, and one financial staff. Results: There were five themes identified based on the findings, namely; the actions undertaken for preventing complaints, the actions undertaken for resolving complaints, the hospital service improvement, the factors influencing preventive actions and complaint fulfillment, and the expectations in the prevention and fulfillment of complaints. The result showed that if the management complaints were taken attention of the action undertaken for resolving complaint and professional, customer complaint management would have been increase patients’ satisfaction.